Esej in interdiskurzivnost - Juvan, Marko (Primerjalna književnost, 2010)
Exchanges between various areas of knowledge are typical of the transversal discourses in literature and journalism. As a genre, the essay excels in its interdiscursivity, which is inscribed in the text in the form of singularity. However, the singular configuration of sense, which in the essay embodies Kant's notion of the "aesthetic idea" and transcends the existing cultural codes and knowledge systems from which it generally proceeds, would not be possible without a sensus communis - that is, a concept of common place, or referring to common sense or Kant's Gemeinsinn, which is the prerequisite for aesthetic judgment. This bipolarity of the essay is elucidated from the perspective of the social history of knowledge and within the context of this genre's relationship to the press, books, and newspapers.
Keywords: Rožanc, Marjan, 1930-1990; Jančar, Drago, 1948-; literarni žanri; esej; singularnost; interdiskurzivnost; estetska sodba; sensus communis